Emerging Targets for the Treatment of Primary Sclerosing Cholangitis - Tatscher, Elisabeth; Mady, Samy; Fickert, Peter (Seminars in Liver Disease, 2025)
Primary sclerosing cholangitis (PSC) is a rare, progressive cholestatic disease of unknown etiology and characterized by inflammation and stricturing of intrahepatic and/or extrahepatic bile ducts. This process leads to bile duct scarring, progressive liver fibrosis, and end-stage liver disease. PSC is often associated with a specific form of inflammatory bowel disease and patients face a significant risk of developing cholangiocarcinoma and colorectal cancer. The clinical course of PSC can differ significantly between subtypes and affected individuals, representing a major obstacle to successful medical treatment trials. Numerous innovative therapeutic targets have been identified and, at least in part, explored, including nuclear and membrane receptors regulating bile acid metabolism and transport, modulation of gut microbiota, and signaling molecules involved in liver inflammation and fibrosis. Successful drug testing in preclinical PSC models as well as positive signals from some clinical studies justify hope. However, no medical treatment has so far been proven to improve transplant-free survival or overall survival in PSC patients. Disease-modifying drugs are urgently awaited. Despite ongoing efforts to improve study designs and implement treatment trials for novel drug targets, a central breakthrough has not yet been convincingly achieved. This situation might change in the near future. This article summarizes current research efforts aimed at developing medical treatments for PSC.
Keywords: primary sclerosing cholangitis; treatment; NCA; UDCA; FXR